Quantitative Easing versus Helicopter Money - Pyatova, Victoria; Šíma, Ondřej; Hába, Stanislav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
The bachelor thesis examines the impact of the Quantitative Easing on the economies such as the USA, the UK, and the Eurozone, it focuses on the economies conditions and structure that determine the size of the effect. As a result, the analysis has shown a limited impact of unconventional monetary policy in the Euro area as the banking sector performs very poorly comparing to the effective implementation in the US and the UK, where the main role of asset allocation was given to financial market. The new concept called the Helicopter Money is introduced in the paper as a new method for Eurozone countries to boost economic development. The advantages and disadvantages of Helicopter Money are broadly discussed by well-known economists as well as the mechanism of its implementation. The macroeconomics models and theories were applied in order to give a closer look at this concept. The author of this paper sees the high potential for the Eurozone in a short and a long-term on condition that the money drop will be supported by corresponsive fiscal policy.
Vedoucí práce: Ondřej Šíma
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses